Peningkatan Keseimbangan Fisik Lansia dengan Virtual Reality di Komunitas Lansia Yayasan Senior Madani - Sugathot, Aan Ika; Lathifah, Witri; Andriani, Githa; Meisatama, Herta; Putri, Meila Nurlita Maulida (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Aging process contributes to gradual deterioration of sensorimotor function including somatosensory, vestibular, and visual systems which increases the likelihood of balance impairment and falls among older adults. This underscores the urgency of conducting systematic balance assessments and implementing targeted interventions. This community engagement program aimed to evaluate the static balance of older adults using the Romberg Test and to enhance balance ability through Virtual Reality (VR) based training within the Social Club Indonesia community. The program involved coordination with the Senior Madani Foundation, baseline assessment of postural stability, and dynamic balance exercises using VR tennis as a multisensory activity. Twenty-five older adults participated in the program. Romberg Test findings revealed that 18 participants maintained stability with eyes open, whereas only 5 remained stable with eyes closed, while the others demonstrated slight sway progressing to instability. That is indicating reliance on visual input and reduced sensorimotor integration. After three VR training sessions, notable improvements were observed: 20 participants showed better stability with eyes open, and 12 demonstrated improved balance with eyes closed, while the remaining participants continued to experience mild sway to instability. VR training elicited highly positive feedback; participants reported increased confidence, enjoyment, and willingness to move compared to traditional exercises. The activity also fostered social engagement and intrinsic motivation, demonstrated by participants’ interest in acquiring VR devices and seeking physiotherapy services that incorporate digital technologies. Overall, the program successfully improved participants’ training experience, enhanced social interaction, and raised awareness of the importance of continuous balance training for fall prevention in older adults.ABSTRAKPenuaan berdampak pada penurunan fungsi sensorimotor, meliputi sistem somatosensorik, vestibular, dan visual, yang berkontribusi terhadap meningkatnya risiko gangguan keseimbangan dan jatuh pada lansia. Kondisi ini menegaskan perlunya penilaian dan intervensi keseimbangan sebagai langkah preventif. Kegiatan pengabdian masyarakat ini bertujuan menilai kemampuan keseimbangan statis lansia menggunakan Romberg Test serta meningkatkan stabilitas postural melalui latihan berbasis Virtual Reality (VR) di komunitas lansia Social Club Indonesia. Metode mencakup koordinasi dengan pengurus Yayasan Senior Madani, pelaksanaan pengukuran awal Romberg Test, dan pemberian latihan keseimbangan dinamis menggunakan permainan tenis virtual sebagai stimulasi multisensorik. Sebanyak 25 lansia terlibat sebagai peserta. Hasil awal menunjukkan 18 peserta stabil dengan mata terbuka, namun hanya 5 peserta stabil saat mata tertutup, sedangkan sebagian lainnya mengalami goyangan ringan hingga tidak stabil. Setelah tiga sesi latihan VR, terjadi peningkatan nyata: 20 peserta menunjukkan stabilitas lebih baik pada kondisi mata terbuka dan 12 peserta mengalami perbaikan keseimbangan pada kondisi mata tertutup, sedangkan sisanya masih goyang ringan hingga tidak stabil. Respons peserta terhadap latihan VR sangat positif, ditandai meningkatnya kepercayaan diri, motivasi gerak, serta kenyamanan selama sesi latihan dibanding metode konvensional. Selain manfaat fisik, interaksi sosial antar peserta semakin kuat, bahkan beberapa peserta menyatakan minat untuk memiliki perangkat VR dan mengakses layanan fisioterapi berbasis teknologi. Program ini terbukti efektif meningkatkan pengalaman latihan, kesadaran kesehatan, dan keseimbangan fungsional lansia.